TemporalContext-2021-FinWhale - Madhusudhana, Shyam (10524047); Yu Shiu (10524050); Klinck, Holger (10524053); Fleishman, Erica (10524056); Liu, Xiaobai (10524059); Nosal, Eva-Marie (10524062); Helble, Tyler (10524065); Cholewiak, Danielle (10524068); Gillespie, Douglas (10524071); Širović, Ana (10524074); Roch, Marie (10524077) (2021)
This dataset contains representative fin whale (Balaenoptera physalus) acoustic data and annotations to train recognition models using code available at https://github.com/shyamblast/TemporalContext-2021